(untitled) - Ben-Ari, M. (New York, 2006)
Software Engineering: Principles and Practice challenges the reader to appreciate the issues, design trade-offs and teamwork required for successful software development. This new edition has been brought fully up to date, with complete coverage of all aspects of the software lifecycle and a strong focus on all the skills needed to carry out software projects on time and within budget.
Keywords: Parallel processing (Electronic computers),Electronic data processing,Xử lý song song (máy tính điện tử),Xử lý dữ liệu điện tử; Distributed processing,Chế biến phân phối